Does the Gradualness of Leaf Shedding Govern Nutrient Resorption from Senescing Leaves in Mediterranean Woody Plants? (Plant and Soil, 2005)
The resorption of nutrients from senescing leaves is a key component of the nutrient conservation strategy of plants. Despite its relevance, the regulation of the eﬃciency of this process is poorly understood. The aim of this work was to test the hypothesis that species that shed leaves gradually along the year are less eﬃcient reabsorbing nutrients from senescing leaves than species that shed leaves in a short period. N-, P-, and Kresorption-eﬃciencies were measured in 11 Mediterranean species and regressed against an index of the gradualness of leaf shedding. Additionally, the bivariate relations among leaf nutrient content before senescence, nutrient content in senesced leaves, pool of nutrients reabsorbed during senescence, and nutrient resorption eﬃciency, were examined. K-resorption-eﬃciency was markedly lower in species with protracted leaf-shedding, in agreement with the initial hypothesis. This pattern was less signiﬁcant for Nand P-resorption-eﬃciencies. When leaf nutrient content before senescence was high, the amount of nutrients reabsorbed and the amount of nutrients in senesced leaves were high. Consequently, nutrient resorption eﬃciency was unaﬀected by the leaf nutrient status before senescence. It is concluded that the leaf shedding pattern per se inﬂuences nutrient resorption in Mediterranean perennials, irrespective of additional environmental controls. Furthermore, it is suggested that plants diﬀering in nutrient status do not exhibit diﬀerent nutrient resorption eﬃciencies because the nutrient content of leaves before senescence aﬀects the components of resorption eﬃciency in countervailing ways.